2008
DOI: 10.1177/070674370805300306
|View full text |Cite
|
Sign up to set email alerts
|

Disclosure and Social Acknowledgement as Predictors of Recovery from Posttraumatic Stress: A Longitudinal Study in Crime Victims

Abstract: W La Revue canadienne de psychiatrie, vol 53, no 3, mars 2008 160Objective: To address posttraumatic stress disorder (PTSD) predictors with research focused on the coping styles of traumatized individuals.Method: A total of 86 crime victims (mean age 46.1, standard deviation 17.6) were assessed at 5 and 11 months post-crime. Disclosure of trauma, social acknowledgement, dysfunctional posttraumatic cognitions, and PTSD symptom severity were assessed by self-reports.Results: Dysfunctional posttraumatic cognition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

21
120
2
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 93 publications
(144 citation statements)
references
References 25 publications
21
120
2
1
Order By: Relevance
“…Similar results showing that General Disapproval was positively and significantly related to PTSD have been presented by Mueller, Moergeli and Maercker (2008) in a study of crime victims. Schumm et al (2014), who performed structural equation modelling of the results of their study of US military veterans seeking PTSD treatment, found that General Disapproval was positively and significantly related to PTSD, whereas both Recognition and Family Disapproval were not.…”
Section: Discussionsupporting
confidence: 88%
“…Similar results showing that General Disapproval was positively and significantly related to PTSD have been presented by Mueller, Moergeli and Maercker (2008) in a study of crime victims. Schumm et al (2014), who performed structural equation modelling of the results of their study of US military veterans seeking PTSD treatment, found that General Disapproval was positively and significantly related to PTSD, whereas both Recognition and Family Disapproval were not.…”
Section: Discussionsupporting
confidence: 88%
“…Findings of our study also indicated that trauma disclosure might be predicted by social acknowledgment. Several studies indicated possible associations between trauma disclosure and social acknowledgment (4,9), however these associations were not analyzed in detail previously.…”
Section: Discussionmentioning
confidence: 99%
“…Several metaanalysis of trauma disclosure revealed significant positive effects on physical and psychological health outcomes (1,2). Research also indicated that previous disclosure of traumatic events was associated with increased emotional coping, positive life changes after traumatic experience and posttraumatic growth (3), and less posttraumatic stress disorder symptoms (4,5). Research on trauma disclosure was largely influenced by the Pennebaker paradigm which proposed emotional writing as a method of coping with trauma (6).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In relation to family disapproval and recognition, the findings are more diverse, with results indicating that family disapproval is either positively associated with (Maercker & Müller, 2004) or unrelated to PTSD (Sommer et al, 2017b; Jones et al, 2006). Recognition has been revealed to be either negatively related to (Maercker, Povilonyte, Lianova, & Pöhlmann, 2009) or unrelated to PTSD (Mueller, Moergeli, & Maercker, 2008); however, in a South African victim–offender population, a positive relationship between recognition and PTSD was found, as discussed in Sommer et al (2017b). …”
Section: Introductionmentioning
confidence: 96%